Varicella with atypical onset on site of previous vaccination. - Rovatti, G. (European Journal of Pediatric Dermatology, 2008)
A 3-year-old boy was observed because of erythematous and vesicular lesions reminiscent of varicella. The lesions first appeared on the right deltoid region and on the upper third of the right arm. In the same region the lesions were more numerous. According to the history, one week prior to the eruption, the boy had undergone in the right deltoid region vaccination against diphtheria, tetanus and pertussis...